New illustrations, new species and new combination of Hemacroneuria Enderlein (Plecoptera: Perlidae) from China - Huo, Qing-Bo; Zhu, Bin-Qing; Du, Yu-Zhou (Zootaxa, 2021)
Hemacroneuria violacea Enderlein, 1909 is discovered and re-described from four provinces of southern China. A similar new species of Hemacroneuria from the Nanling Mountains is proposed. Meanwhile, Brahmana flavomarginata Wu, 1962 is transferred into Hemacroneuria, and the status of Kiotina spatulata Wu, 1948 is discussed in this paper.